A Model of the Joint Distribution of Banking and Exchange-Rate Crises - Marion, Nancy (IMF Working Papers; Working Paper, 2001)
We develop a simple framework for studying the joint distribution of banking and currency crises triggered by real shocks. Our framework illustrates the fact that bank and currency collapses are related but they are not the same thing. Studying currency and bank collapses either in isolation or in perfect correlation with each other is inappropriate, producing biased estimates of the likelihood of crises.